2020
DOI: 10.1158/1538-7445.am2020-ct127
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT127: A phase I study of cMET inhibitor bozitinib in patients with advanced NSCLC harboring cMET alterations

Abstract: Introduction: Cellular mesenchymal-epithelial transition (cMET) dysregulation has been described in non-small-cell lung cancer (NSCLC) and implicated as a negative prognostic factor. It can occur as amplification, overexpression or mutations leading to exon 14 skipping. Bozitinib (PLB-1001, CBT-101) is a potent highly selective cMET inhibitor, which has demonstrated superior activity in both in vitro and in vivo NSCLC models. Methods: This was a phase I, open-label multicenter study conducted in locally advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Preliminary results from a Phase I, open-label, multicenter study evaluating bozitinib in locally advanced or metastatic NSCLC with MET dysregulation demonstrated that bozitinib had a manageable safety profile at the recommended Phase II dose of 200 mg twice daily ( 120 ). Only eight patients had MET amp NSCLC in this study, and it was not specified if patients had primary or secondary MET amp.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary results from a Phase I, open-label, multicenter study evaluating bozitinib in locally advanced or metastatic NSCLC with MET dysregulation demonstrated that bozitinib had a manageable safety profile at the recommended Phase II dose of 200 mg twice daily ( 120 ). Only eight patients had MET amp NSCLC in this study, and it was not specified if patients had primary or secondary MET amp.…”
Section: Resultsmentioning
confidence: 99%
“…The most common AE is peripheral edema, observed in 32% to 74% of patients, whereas grade greater than or equal to 3 peripheral edema is observed in 9% to 21% of patients. 44 , 46 , 54 , 55 , 56 Efficient management of drug-related AEs is markedly associated with treatment outcomes. Nonpharmacologic management of peripheral edema includes bed or foot elevation, compression stockings, massage, reduced salt intake, and exercise.…”
Section: Updated Landscapes Of Met Tkismentioning
confidence: 99%
“…There are also other nitrogen heterocycles that have been successfully used in the design of type Ib MET inhibitors (Figure B), such as benzothiazole ( 64 ) and 2-methylindazole ( 65 ). , Among them, the highly selective bozitinib ( 65 ) exhibited potent inhibitory activity against MET and MET-dependent cell lines in vitro. In phase I, it has shown preliminary antitumor activity in patients with exon 14 skipping and/or amplification, with an ORR of 30.6%, and a DCR of 94.4% . Currently, phase II is underway (NCT04258033)…”
Section: Small Molecule Inhibitors Of Metmentioning
confidence: 99%
“…In phase I, it has shown preliminary antitumor activity in patients with exon 14 skipping and/or amplification, with an ORR of 30.6%, and a DCR of 94.4%. 115 Currently, phase II is underway (NCT04258033). 116 In addition to the bicyclic hinge binders, the monocyclic pyrimidine group has also been successfully used for designing type Ib inhibitors, such as tepotinib (4) reported by Merck.…”
Section: Small Molecule Inhibitors Of Metmentioning
confidence: 99%